Migration of cations in layered oxides for creating a highly active interface toward CO preferential oxidation. Issue 21 (11th May 2021) - Ding, Junfang; Geng, Zhibin; Li, Liping; Wang, Ye; Zuo, Ying; Li, Huixia; Yang, Min; Li, Guangshe
Abstract : Migration and doping of cations create a highly active interface in CeO2 –CuCoO2 composite. Abstract : Rational design and integration of collaborative active species at an interface is a crucial issue for the development of advanced materials. In this work, we present a simple interlayer cation migration strategy utilizing the unique layered structure of CuCoO2 to controllably construct an active interface. CuCoO2 –CeO2 composites with a strongly coupled heterojunction interface were initially synthesized by an incipient wetness impregnation process and subsequent calcination, during which a large amount of Cu n + takes interlayer as a channel, migrating to the interface of the composite and even partially dope into the CeO2 lattice due to charge imbalance. The composites were systematically characterized using TEM/HRTEM, ICP, XRD, XPS, Raman spectra, H2 -TPR, O2 -TPD, and in situ DRIFTS measurements. As the CeO2 content in the composites increases, the Ce 3+ content and surface areas of the samples increase gradually, and the Ce 3+ content reached a maximum in 70%CeO2 –CuCoO2 . Meanwhile, the migration of interlayered Cu n + results in the generation of many oxygen vacancies and active CuO x enriched at the interface, which promoted the activation of oxygen, adsorption of CO and redox ability of CeO2 –CuCoO2 composites, thus optimizing the reaction path. Creating a strongly coupled heterojunction interface and inducing interfacial Cu n + site enrichment significantly improve the catalytic oxidation activity of CO preferential oxidation (CO-PROX) at low temperatures ( i.e. CO conversion more than 95.0% at even 120 °C), much better than a physically mixed CeO2 and CuCoO2 sample (CO conversion about 90.0% at 220 °C). This work indicates that irreversible cation migration in layered oxide materials could be used for the fabrication of highly active catalysts.